Diabetic retinopathy - A Kittantong (Journal of Health Science and Medical Research (JHSMR), 2006)
Diabetes mellitus is a major health problem of Thailand. A major complication of diabetes mellitus is diabetic retinopathy, which is a common cause of visual loss and blindness in diabetic patients. The physician plays a most important role in management for referring diabetic patients to ophthalmologists for an eye examination and advising them on controlling blood sugar to slow the progression of diabetic retinopathy.